|
|- p -> (q -> p)
-
p
:
formula<fol>
-
q
:
formula<fol>
-
Returns:
thm
|
|
|- (!x. p -> q) -> (!x. p) -> (!x. q)
-
x
:
string
-
p
:
formula<fol>
-
q
:
formula<fol>
-
Returns:
thm
|
|
|- p /\ q <-> (p -> q -> ⊥) -> ⊥
-
p
:
formula<fol>
-
q
:
formula<fol>
-
Returns:
thm
|
|
|- (p -> q -> r) -> (p -> q) -> (p -> r)
-
p
:
formula<fol>
-
q
:
formula<fol>
-
r
:
formula<fol>
-
Returns:
thm
|
|
|- ((p -> ⊥) -> ⊥) -> p
-
p
:
formula<fol>
-
Returns:
thm
|
|
|- t = t
-
t
:
term
-
Returns:
thm
|
|
(?x. p) <-> ~(!x. ~p)
-
x
:
string
-
p
:
formula<fol>
-
Returns:
thm
|
|
|- (?x. x = t) [provided x not in FVT(t)]
-
x
:
string
-
t
:
term
-
Returns:
thm
|
|
|- s1 = t1 -> ... -> sn = tn -> f(s1, ..., sn) = f(t1, ..., tn)
-
f
:
string
-
lefts
:
term list
-
rights
:
term list
-
Returns:
thm
|
|
|- (p <-> q) -> p -> q
-
p
:
formula<fol>
-
q
:
formula<fol>
-
Returns:
thm
|
|
|- (p <-> q) -> q -> p
-
p
:
formula<fol>
-
q
:
formula<fol>
-
Returns:
thm
|
|
|- p -> !x. p [provided x not in FV(p)]
-
x
:
string
-
p
:
formula<fol>
-
Returns:
thm
|
|
|- (p -> q) -> (q -> p) -> (p <-> q)
-
p
:
formula<fol>
-
q
:
formula<fol>
-
Returns:
thm
|
|
|- ~p <-> (p -> ⊥)
-
p
:
formula<fol>
-
Returns:
thm
|
|
|- p \/ q <-> ~(~p /\ ~q)
-
p
:
formula<fol>
-
q
:
formula<fol>
-
Returns:
thm
|
|
|- s1 = t1 -> ... -> sn = tn -> f(s1, ..., sn) = f(t1, ..., tn)
-
p
:
string
-
lefts
:
term list
-
rights
:
term list
-
Returns:
thm
|
|
|- ⊤ <-> (⊥ -> ⊥)
-
Returns:
thm
|
|
maps a theorem back to the formula that it proves
-
arg0
:
thm
-
Returns:
formula<fol>
|
|
generalization (proper inference rule)
|- p ==> !x. p
-
x
:
string
-
arg1
:
thm
-
Returns:
thm
|
|
modusponens (proper inference rule)
|- p -> q |- p ==> |- q
-
pq
:
thm
-
arg1
:
thm
-
Returns:
thm
|